An Application of Blake and Mouton’s Leadership Styles of Seminarians of Saint Joseph Major Seminary In Ho Chi Minh City Diocese during Serving at Parish - Van Trong, Pham (Scholar: Human Sciences, 2014)
The purpose of this study was to use the theory of Blake and Mouton’s leadership Grid to measure seminarians’ behaviors in when they served at parishes. The objectives were (1) to determine the leadership styles the seminarians applied during serving at parish; (2) to examine relationship between seminarians’ leadership styles and their demographic profile; (3) to compare the difference in Team leadership styles among age groups, diocese groups, educational attainment groups, and work experience groups. The research method using in this study was quantitative. A Likert scale uestionnaire which based on Blake and Mouton’s leadership Grid theory was used to determine leadership styles of 168 seminarians of five classes from three dioceses at Saint Joseph Major Seminary of Ho Chi Minh City diocese. The data from questionnaire was analyzed by using SPSS program. The findings of this study demonstrated that there was a dominant leadership style the seminarians applied during serving at parish; seminarians’ leadership styles were no related to age, diocese, educational attainment, and work experience; Team leadership style of seminarians were no significantly different among age groups, diocese groups, educational attainment groups, and work experience groups.